1989
DOI: 10.1259/0007-1285-62-735-241
|View full text |Cite
|
Sign up to set email alerts
|

Radiobiological assessment of permanent implants using tumour repopulation factors in the linear-quadratic model

Abstract: By combining existing linear-quadratic equations relating to decaying-source therapy with an assumed tumour repopulation factor, it has been possible to devise a method for the radiobiological assessment of permanent implants. For calculation purposes there is a time after which an implant can no longer be considered effective in sterilizing tumour cells. This "effective" treatment time for a permanent implant can be approximately defined in terms of the radionuclide decay constant, the potential doubling time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
92
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(94 citation statements)
references
References 6 publications
0
92
0
2
Order By: Relevance
“…118,119 This model was used by Ling et al to examine the effect of dose heterogeneity in prostate seed implants. 96 The authors concluded that there might be some advantage in dose heterogeneity at about 20% above the prescribed dose, but beyond that, dose would be ''wasted'' in terms of producing cell kill.…”
Section: Biological Modelsmentioning
confidence: 99%
“…118,119 This model was used by Ling et al to examine the effect of dose heterogeneity in prostate seed implants. 96 The authors concluded that there might be some advantage in dose heterogeneity at about 20% above the prescribed dose, but beyond that, dose would be ''wasted'' in terms of producing cell kill.…”
Section: Biological Modelsmentioning
confidence: 99%
“…Nevertheless, for this evaluation, two-fraction protocols with shorter time delays remain more interesting than a single injection; for evaluation E3, this increase is superior to 8.8% and 5.7% (minimum increases obtained for a 24h time delay) for the MIA and BED mean,TL , respectively, compared with the values obtained for a single injection, and reaches 9.5% and 10.9% for BED mean,TL for time delays superior to 3 and 7 days, respectively. Moreover, the potential of shortening time delays between fractions could be further enhanced by taking into account a repopulation constant for the different ROIs in the calculation of the BED distribution (Dale, 1989). The best number of fractions and time delay between fractions that would keep the absorbed dose rate high enough to compensate for cancerous cell repopulation could then be determined using optimization tools.…”
Section: Discussionmentioning
confidence: 99%
“…We also recalculated the biologically equivalent dose (BED) of this treatment, taking into account repair and repopulation of breast tissues (14,15), and obtained with an alpha/beta ratio of 10 Gy for early and tumor effects a BED in Gy 10 that is similar to the classical 16 Gy boost in eight fractions. The BED in Gy 3 for late effects in healthy tissues seems, on the other hand, to be higher than for the classical external approach.…”
Section: Discussionmentioning
confidence: 99%
“…When applying this technique for partial breast irradiation, the prescription dose will have to be calculated taking into account the biologic behavior of breast cancer cells (14,15). The BED of a very low dose rate partial breast irradiation should be at least equivalent to the BED of a classical 50 Gy treatment in 25 fractions over 5 weeks.…”
Section: Discussionmentioning
confidence: 99%